The benefits of the use of gametherapy with the elderly - Santos, Carla Chiste Tomazoli; Meira, Luis Gustavo da Silva; Sabiá, Gabriel Alves (Revista Coleta Científica, 2021)
Currently within Brazilian society, we have had a large increase in the demographic number of elderly people, together with a great leap in technology, taking into account that many elderly people fear or even have difficulties in understanding how to use such electronic devices, physiotherapy can act with the use gametherapy that is gaining more and more space dedicated to the elderly making it possible to work on balance, physical conditioning, aerobics and cognitive stimulation, games produce movements similar to what we do within conventional physiotherapy, taking into account the dynamism and the interactive way that the patient visualizes their evolution, passing the level and earning more points, making the treatment lighter and more humanized